2012
DOI: 10.3233/jad-2012-120025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cognitive Domains, Physical Performance, and Gait in Elderly and Demented Subjects

Abstract: Cognitive function declines with age, with studies linking decreases in cognitive function to increased fall risk. The association between declines in specific cognitive domains and the development of gait and physical performance deficits has not been established. The current cross-sectional study was designed to address these issues using well characterized control subjects (n = 50), and individuals with early stage dementia (n = 50) tightly matched for age, gender, and education. All participants received d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 0 publications
8
53
2
3
Order By: Relevance
“…As expected, we also found an association between change in dual-task performance and SDMT. This finding is congruent with previous crosssectional studies in patients with all-cause dementia where dual-task performance and cognitive performance are associated [11,25,43,44]. Abbreviations: MMSE, mini mental state examination range from 0 (severe impairment) to 30 (no impairment); SDMT, Symbol Digit Modalities Test are the number of correct matches in 120 sec, with a higher score indicating a higher level of mental speed and attention; NPI, Neuropsychiatric Inventory range from 0 to 144, with higher scores indicating increased behavioral and psychological symptoms; PASE, Physical activity scale for the elderly, with higher scores indicating higher levels of habitual physical activity.…”
Section: Discussionsupporting
confidence: 94%
“…As expected, we also found an association between change in dual-task performance and SDMT. This finding is congruent with previous crosssectional studies in patients with all-cause dementia where dual-task performance and cognitive performance are associated [11,25,43,44]. Abbreviations: MMSE, mini mental state examination range from 0 (severe impairment) to 30 (no impairment); SDMT, Symbol Digit Modalities Test are the number of correct matches in 120 sec, with a higher score indicating a higher level of mental speed and attention; NPI, Neuropsychiatric Inventory range from 0 to 144, with higher scores indicating increased behavioral and psychological symptoms; PASE, Physical activity scale for the elderly, with higher scores indicating higher levels of habitual physical activity.…”
Section: Discussionsupporting
confidence: 94%
“…cognitive or mobility impairments and the presence of comorbidities [19,20,21,22]. In this study, we showed that this relation is also present in community-dwelling elderly visiting the geriatric outpatient clinic with common comorbidities and mobility impairments.…”
Section: Discussionsupporting
confidence: 48%
“…These studies showed that a lower cognitive status is associated with a lower ability to maintain standing balance [19,20,21,22] and with increased center of pressure (CoP) movement [15,23,24]. CoP movement is a measure for the steadiness of the body while maintaining balance and is assessed using a force plate, which measures the ground reaction forces.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment and dementia are strong predictors of declines in gait speed 40 and poorer SPPB. 41 Depression is another associated diabetes comorbidity that contributes to ADL and mobility disability. 42 Prevalence of depressive symptoms is higher in people with diabetes than in their nondiabetic counterparts.…”
Section: Factors Explaining the Association Of Diabetes With Functionmentioning
confidence: 99%